Safety and tolerability of fluvastatin XL in the treatment of hyper-cholesterolemia : a postmarketing surveillance conducted in Indonesia (Medical Journal of Indonesia, 2008)
Fluvastatin XL 80 mg tablet has been marketed in Indonesia since December 2002. This post-marketing surveillance (PMS) was conducted between May 2004 and April 2005 involving 98 general physicians to observe the safety and tolerability of fluvastatin XL 80 mg once daily at bedtime for 8 weeks in the treatment of outpatients with hypercholesterolemia. The efficacy of the drug in lowering LDL-cholesterol and other lipid parameters was also observed in daily clinical practice in this PMS. A total of 740 patients were eligible for safety analyses. There were 32 patients (4.32%) with 39 adverse events that were considered related to fluvastatin XL therapy. The most common adverse reactions were dizziness (2.03%), nausea (1.22%), and myalgia (0.68%). No serious adverse event (SAE) was found in this PMS, and no patient discontinued due to adverse event. According to physician's global evaluation, the safety and tolerability of treatment was good in 91.9% of patients. For efficacy analyses, only 566 patients were eligible. At week 8, fluvastatin XL caused decreases in LDL-cholesterol (LDL-C), total cholesterol (TC) and triglyceride (TG) levels by 28.6%, 30.2% and 24.5%, respectively, and an increase in HDL-cholesterol (HDL-C) by 14.3%. In 74 patients with baseline TG > 300 mg/dL, the decrease in TG was 38.1% and the increase in HDL-C was 18.1%. Reduction in LDL-C of > 40% occurred in 19.6% of the patients. In conclusion, treatment with fluvastatin XL 80 mg once daily for 8 weeks in this PMS was shown to be safe and well tolerated, and also effective in reducing LDL-C, TC and TG, and raising HDL-C in daily clinical practice. (Med J Indones 2008; 17:88-95)